Sustainable Urban Development in West Africa: A Rapid Review of Challenges and Opportunities - (:unkn) unknown (My University, 2025)
Background: The rapid urbanization witnessed across West Africa presents an urgent need to address sustainable urban development. Objective: This rapid review synthesizes the existing literature on the challenges and opportunities related to sustainable urban development in West Africa. It seeks to clarify the key factors influencing regional urban sustainability and identify practical pathways for policy and planning interventions. Methods: We reviewed peer-reviewed journal articles published between 2015 and 2025 identified through Web of Science, Environment Complete, Energy & Power Source, Engineering Source, Academic Search Ultimate, and CINAHL Ultimate. Of the 23 studies, 6 articles were selected for the review. A thematic analysis was then used to code and categorize the data, resulting in emergent themes showing the challenges and prospects for sustainable urban development. Results and Conclusion: The findings show that West African cities face formidable challenges, including under-resourced infrastructure, weak policy coordination, entrenched social inequalities, and mounting environmental pressures. Nevertheless, there are also promising opportunities, such as leveraging technological innovations to improve service delivery, implementing policy initiatives aimed at decentralization, enhancing stakeholder engagement, and integrating nature-based solutions into urban planning. Future research should broaden its geographic coverage and employ longitudinal or comparative methods to evaluate the long-term impact of policy and planning interventions.
Keywords: African Research